2014
DOI: 10.4028/www.scientific.net/amr.979.220
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of YBa<sub>3</sub>Cu<sub>4</sub>O<sub>x</sub> Superconductor and Comparison with YBa<sub>2</sub>Cu<sub>3</sub>O<sub>x</sub>

Abstract: In this research, the Y123 (YBa2Cu3Ox) and Y134 (YBa3Cu4Ox) superconductors were synthesized by solid state reaction and melt process, respectively. The crystal structure of all the samples were then determined using the Rietveld full-profile analysis method to indicate orthorhombic structure. The resistivity measurements showing Tc onset of Y123 lower than Y134 for solid state reaction but higher than Y134 melt process. However, the critical temperature off-set of Y134 has lower than of Y123. The SEM and EDX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…The melt process of YBaCuO has been used for improve the texture of bulk sample that can fulfill the requirement of bulk YBaCuO on the commercial application. Recently, the Y134 (YBa 3 Cu 4 O x ) superconductor was synthesized both by solid state and melt process and found that the solid-state-reaction-sample showed more critical temperature and more pores than the melt-process-sample [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The melt process of YBaCuO has been used for improve the texture of bulk sample that can fulfill the requirement of bulk YBaCuO on the commercial application. Recently, the Y134 (YBa 3 Cu 4 O x ) superconductor was synthesized both by solid state and melt process and found that the solid-state-reaction-sample showed more critical temperature and more pores than the melt-process-sample [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of increasing Ti content YBaCuO is equivalent to that of decreasing oxygen content in YBaCuO that the lowering of critical temperature with increasing Ti content. Chainok et.al [9] studied the Y123 (YBa 2 Cu 3 O x ) and Y134 (YBa 3 Cu 4 O x ) superconductors synthesized by solid state reaction and melt process. The crystal structures of the samples were orthorhombic structure.…”
Section: Introductionmentioning
confidence: 99%